The Chameleon's Ambition for Power in the Film Kung Fu Panda 4 - Muhammad Rosul; Novi Sriwulandari; Risma Kartika Dewi (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study examines The Chameleon’s ambition for power in the animated film Kung Fu Panda 4 by treating the film as a narrative text. The Chameleon is portrayed as a sorceress and shape‑shifting villain who seeks to seize Po’s Staff of Wisdom and use it to absorb the chi of past kung fu masters in order to become the most powerful ruler in the kung fu world. Her ambition is closely connected to her earlier experiences of rejection and underestimation due to her small body and non‑traditional appearance as a kung fu practitioner. The research aims to describe how The Chameleon’s ambition for power is constructed through characterization, and how this ambition functions within the narrative structure of the film. A qualitative descriptive approach is employed, using Abrams and Harpham’s characterization theory, particularly the showing and telling methods, as the main analytical framework. Data are taken from selected scenes and dialogues that reveal The Chameleon’s motivations, strategies, and interactions with other characters, especially Po and Zhen. The findings indicate that her ambition is expressed through strategic planning, manipulation, and the instrumental use of magic and others’ abilities. Her ambition not only shapes her identity as a villain, but also drives the central conflict and highlights thematic issues related to power, recognition, and self‑worth in the film. These results suggest that ambition for power can be read as a complex narrative device rather than a merely individual psychological trait in contemporary animated cinema.